Shatter me - Mafi, Tahereh (New York : Harper, 2012)
Ostracized or incarcerated her whole life, seventeen-year-old Juliette is freed on the condition that she use her horrific abilities in support of The Reestablishment, a postapocalyptic dictatorship, but Adam, the only person ever to show her affection, offers hope of a better future.
Keywords: Ability -- Fiction; Science fiction